Ultrastructure and lectin characterization of granular salivary cells from Ixodes ricinus females - Vancová, Marie; Zacharovová, Klára; Grubhoffer, Libor; Nebesářová, Jana (The Journal of parasitology, 2006)
A site-specific glycosylation of salivary glands (SGs) isolated from unfed and partially fed Ixodes ricinus females was identified with the use of lectin affinity labeling on sections and western blots of SDS-PAGE gels. The results revealed that secretory granules of a, b, and c cells of the type II acinus and e and f cells of the type III acinus are glycosylated. In partially engorged tick SGs, 2 subtypes of c cells were distinguished. The granules of c1 cells contained mannose, N-acetyl-D-glucosamine, and sialic acid residues. The granules of b, c2, and e cells exhibited complex glycoconjugates rich in mannose, N-acetyl-D-glucosamine, galactose, N-acetyl-D-galactosamine, and a moderate amount of sialic acid. The granules of f cells contained N-acetyl-D-glucosamine and mannose moieties. Type III acini surfaces were covered with mannose-specific ConA binding sites. Except the granules of salivary cells, sialic acid-specific lectins MAA II and SNA strongly bound cuticular structures of alveolar ducts, and weakly with the cuticular spiral thread of excretory salivary ducts. The total sialic acid level in SG homogenates isolated from partially fed females was determined by the thiobarbituric acid method. Sialic acid, which has been found during the development of a few insect species, has not been reported in ticks as yet.
Keywords: elektronová mikroskopie; Lectins; zvířata; lektiny; Financing, Organized; Microscopy, Electron; financování organizované; Carbohydrates; sacharidy; Glycosylation; klíště; Salivary Glands; Microscopy, Fluorescence; slinné žlázy; ženské pohlaví; Female; Secretory Vesicles; Animals; kyselina N-acetylneuraminová; sekreční vezikuly; glykosylace; N-Acetylneuraminic Acid; fluorescenční mikroskopie; Ixodes